CULTURAL-GEOGRAPHIC DETERMINANTS OF JERUSALEM - Medojević, Jovo (Bulletin of Natural Sciences Research, 2017)
Culture and cultural phenomena are always in the focus of studying cultural geography. The study of Jerusalem from the aspect of supranational spread of culture is a special challenge. The cultural-geographical determinants of Jerusalem represent the features seen through the factors of time and space in which Jerusalem became and survived. The study of the morphology of cultural-geographical determinants in Jerusalem represents scientifically study of the relationship between man and his environment, the man's belief and application of perception of cultural-geographic determinants.
Keywords: Cultural-geography; Jerusalem; pilgrimage